68Ga-PSMA-HBED-CC–Avid Synchronous Urinary Bladder Paraganglioma in a Patient With Metastatic Prostate Carcinoma. (September 2018) - Parihar, Ashwin Singh; Vadi, Shelvin Kumar; Mittal, Bhagwant Rai; Kumar, Rajender; Bal, Amanjit; Singh, Shrawan Kumar
Abstract : Abstract: 68 Ga-PSMA-HBED-CC PET/CT has proven to be a useful modality in patients with prostate carcinoma, especially in those with suspected recurrence and in detection of locoregional and distant metastases. However, with expanding use of this tracer, several recent reports of in vivo expression of PSMA in nonprostatic benign and malignant entities have been published. We report a patient with PSMA-avid synchronous urinary bladder paraganglioma and metastatic prostate carcinoma.